Some Historical Ethnic Rulers of South Kamrup on the Eve of the Neo-Vaishnava Movement - Dr. Nara Kanta Adhikary (International Journal of Advanced Science and Technology, 2020)
The mighty river Brahmaputra flows through the middle of the present Kamrup district of Assam. The area located in the southern bank of the river Brahmaputra of Kamrup district is called South Kamrup . In the various stages of history, South Kamrup played an important role. In the past, South Kamrup was known as Dakhin kul or Dakshin kul (Dakhin = South, kul = bank). Mentioning of the term Dakhin kul or South Kamrup is found in various times and places of history. For the first time the mentioning of Dakhin Kul is found in the Arthasastra of Kautilya.It is in the Arthasastra that the kings of North India built up the commercial relations with Dakhin Kul of Lohit Sagar (River Brahmaputra) through the Kiratas.1 The Copper Plate Inscription of Balavarmadeva of 9th century A.D., the Carit Puthis of Neo-Vaishnavite literature, Pargana Settlements of the Mughals, English writers A.J.M. Mills and E.A. Gait had also used the term Dakhin Kul or South Kamrup is very wide. But under present circumstances the boundary of South Kamrup is much narrow. According to the intelectual group even the greater Guwahati, the present capital city of Assam, is not within the perview of this articulated area.2 In the present record the area is covered by the southern part of the Brahmaputra of Kamrup district covering the area from Dharapur in the East, Sakhati-Nagarbera in the West, Palashbari in the North and Candubi Bil in the South. The whole area is generally identified as South Kamrup.3